Erratum to: Measurements of W and Z boson production in pp collisions at s = 5.02 TeV with the ATLAS detector (The European Physical Journal C, (2019), 79, 2, (128), 10.1140/epjc/s10052-019-6622-x) - Santos, S. P. Amor dos (2019)
It has been found that the theoretical predictions for W and Z boson cross sections, and for the W boson charge asymmetry, which are labelled as NNPDF3.1 [1] have in fact been calculated using the NNPDF3.0 PDF set [2] instead.